2010
DOI: 10.1016/j.neuropsychologia.2010.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Affiliative behavior in Williams syndrome: Social perception and real-life social behavior

Abstract: A frequently noted but largely anecdotal behavioral observation in Williams syndrome (WS) is an increased tendency to approach strangers, yet the basis for this behavior remains unknown. We examined the relationship between affect identification ability and affiliative behavior in participants with WS relative to a neurotypical comparison group. We quantified social behavior from selfjudgments of approachability for faces, and from parent/other evaluations of real life. Relative to typical individuals, partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
64
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 55 publications
9
64
0
Order By: Relevance
“…These findings support studies which have demonstrated heterogeneity in WS (Järvinen-Pasley et al, 2010;Porter et al, 2007;Stojanovik, Perkins & Howard, 2006;Porter & Coltheart, 2005). Interestingly there was variability in age and IQ within clusters, indicating that developmental variables did not consistently or reliably predict RUNNING HEAD: Social Approach in Williams syndrome 19 SAB profiles.…”
Section: Heterogeneity In Wssupporting
confidence: 83%
See 4 more Smart Citations
“…These findings support studies which have demonstrated heterogeneity in WS (Järvinen-Pasley et al, 2010;Porter et al, 2007;Stojanovik, Perkins & Howard, 2006;Porter & Coltheart, 2005). Interestingly there was variability in age and IQ within clusters, indicating that developmental variables did not consistently or reliably predict RUNNING HEAD: Social Approach in Williams syndrome 19 SAB profiles.…”
Section: Heterogeneity In Wssupporting
confidence: 83%
“…However, Porter et al (2007) and Järvinen-Pasley et al (2010) observed substantial variability in the approachability ratings given by individuals with WS which differed from the consistency of ratings demonstrated in the TD control groups. Many developmental disorders are heterogeneous (Abrahams & Geschwind, 2008) and this is a particularly pertinent feature of WS, with cognitive, social, genetic and physical characteristics varying considerably from one individual to the next (Porter & Coltheart, 2005).…”
Section: Heterogeneity Of Social Behaviours In Williams Syndromementioning
confidence: 58%
See 3 more Smart Citations